2022
DOI: 10.3390/ijerph192316195
|View full text |Cite
|
Sign up to set email alerts
|

The Nexus between Green Perceived Quality, Green Satisfaction, Green Trust, and Customers’ Green Behavioral Intentions in Eco-Friendly Hotels: A Structural Equation Modeling Approach

Abstract: With the growing awareness of the climate change effects, hotel customers progressively intend to favor green products and services that minimize adverse environmental effects. The key factors affecting customers’ green behavioral intentions in the hospitality industry context are still under research. Accordingly, this study primarily aims at empirically investigating the nexus between green perceived quality (GPQ), green satisfaction (GS), green trust (GT), and customers’ green behavioral intentions (CGBIs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 83 publications
0
14
1
Order By: Relevance
“…The verification of the mediating effect of perceived value and customer satisfaction is important in this study. In this study, the direct effect between perceived quality and travel intention is not verified; although, previous studies find a direct effect (Hou et al, 2021;Wasaya et al, 2021;Hashish et al, 2022). Research on the mediating effect of perceived value and customer satisfaction on the relationship between perceived quality and travel intention during the COVID-19 pandemic is insufficient.…”
Section: The Mediating Role Of Perceived Value and Satisfactioncontrasting
confidence: 69%
“…The verification of the mediating effect of perceived value and customer satisfaction is important in this study. In this study, the direct effect between perceived quality and travel intention is not verified; although, previous studies find a direct effect (Hou et al, 2021;Wasaya et al, 2021;Hashish et al, 2022). Research on the mediating effect of perceived value and customer satisfaction on the relationship between perceived quality and travel intention during the COVID-19 pandemic is insufficient.…”
Section: The Mediating Role Of Perceived Value and Satisfactioncontrasting
confidence: 69%
“…In the hotel context, the study of Su and Swanson (2019) suggested that organisational GT and identification partially mediated the relationship between CSR and both employee well‐being and green behaviour. Likewise, Hashish et al (2022) acknowledged the partial mediation effect of GT and customer satisfaction on the nexus between green perceived quality of Egyptian hotels and GCB. Despite these results, the mediating role of GT on external and internal CSR and GCB is still sparse, particularly in the hospitality setting, thus reflecting a gap in knowledge that this study aims to bridge.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Tourist implementation intentions for an eco-friendly hotel have been addressed broadly, particularly the tourist willingness to pay and stay in environmentally friendly hotels, spreading positive word-of-mouth to their friends and family [14]. In terms of the concept of perceived value and satisfaction theory, several empirical and theoretical studies have examined and investigated tourists' behavioral intentions toward eco-friendly hotels [3,10,[17][18][19][20]. Additionally, eco-friendly hotels have been studied to recognize the influence on tourist behavior and intention to visit the eco-friendly hotel.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies examined and investigated perceived value and tourist satisfaction in varied contexts [3,5,7,9,11,17,18]. In addition, previous studies have shown that perceived value and satisfaction affect behavioral intentions in the new knowledge of different contexts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation